Russian Federation : 2007 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
The staff report for the 2007 Article IV Consultation highlights the Russian Federation's long-term perspective, economic developments, and macroeconomic policies. Russia's economic growth remains robust. High oil prices and sound fiscal policy underlie Russia's long spell of robust growth. Executive Directors noted that Russia continues to face tensions in the policy mix designed to reduce inflation while preserving exchange rate stability. Raising investment levels is particularly important in light of the projected decline in the labor force and the declining prospect for continued high productivity gains over the medium term.